Analisis Hukum Terhadap Legalitas dan Implikasi Ekspor Pasir Laut Dalam Perspektif Hukum Tata Ruang dan Peraturan Pemerintah Nomor 26 Tahun 2023 - Faturachman, Fauzan Azima; Anjani, Maudy; Zacharias, Vasco Javarison; Maita, Rafel; M, Mahipal (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The exploitation of marine sand as a high-value natural resource has sparked debate in Indonesia, particularly after the issuance of Government Regulation Number 26 of 2023, which regulates the export of marine sand. This policy legally permits the export of marine sand under specific conditions, yet concerns arise regarding its impact on coastal ecosystems and spatial planning, potentially disrupting environmental balance and affecting coastal communities. This study aims to assess the legality of this policy from the perspective of spatial and environmental law and to analyze its implications for marine environmental sustainability. Using a normative juridical approach, the research examines relevant regulations and legal principles. Findings indicate that although the marine sand export policy is legally grounded, its implementation poses significant risks of marine ecosystem degradation, coastal erosion, and changes to coastal spatial planning. Therefore, strict monitoring of this policy is essential to mitigate adverse environmental impacts.